2019
DOI: 10.3390/pharmaceutics11040178
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Effects of the Exposure of Breast Cancer Cell Lines to Different Ratios of Free or Co-Encapsulated Liposomal Paclitaxel and Doxorubicin

Abstract: Background: Associating paclitaxel (PTX) to doxorubicin (DXR) is one of the main chemotherapy strategies for breast cancer (BC) management. Protocols currently available consist in administering both drugs on their maximum tolerated dose, not taking into account the possible differences in efficacy due to their combination ratio. In the present study, the short and long-term cytotoxic effects as well as migratory effects of PTX, DXR, and its combinations at 10:1; 1:1 and 1:10 PTX:DXR molar ratios either free o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
3
7
0
Order By: Relevance
“…The effects of RLX-EMLs, RLX, and blank EMLs on MCF-7 cells viability were evaluated using MTT assay as previously described [ 32 , 33 ]. The cells were plated at a density of 5 × 10 3 cells per well in 96-well plate, and kept in the incubator overnight prior to exposition to the treatments with RLX-EMLs and RLX at different concentrations: 100, 25, 6.25, 1.56, and 0.39 µg/mL for 48 h. RLX was dissolved in 0.1% DMSO and this vehicle concentration showed negative cytotoxic effect on MCF-7 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of RLX-EMLs, RLX, and blank EMLs on MCF-7 cells viability were evaluated using MTT assay as previously described [ 32 , 33 ]. The cells were plated at a density of 5 × 10 3 cells per well in 96-well plate, and kept in the incubator overnight prior to exposition to the treatments with RLX-EMLs and RLX at different concentrations: 100, 25, 6.25, 1.56, and 0.39 µg/mL for 48 h. RLX was dissolved in 0.1% DMSO and this vehicle concentration showed negative cytotoxic effect on MCF-7 cells.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the MTT results, the clonogenic results revealed that the number of MDA-MB-231 colonies formed after extract treatment was not the lowest of the cell tested. This could be due to the surviving cells retaining a greater ability to proliferate, which is similar to a previous finding (Franco et al. , 2019).…”
Section: Resultssupporting
confidence: 90%
“…In contrast to the MTT results, the clonogenic results revealed that the number of MDA-MB-231 colonies formed after extract treatment was not the lowest of the cell tested. This could be due to the surviving cells retaining a greater ability to proliferate, which is similar to a previous finding (Franco et al, 2019). In addition, Kim et al (2015) have previously demonstrated that cell density also affects the growth rate of MDA-MB-231 cancer cells by modulating gene expression.…”
Section: P Indica Induces Ros To Inhibit Cancer Cellssupporting
confidence: 85%
“…Many studies have been done on MDA-MB-231 cell colony formation in the presence of drugs used for triple-negative breast cancer treatment, novel compounds, or their combinations. Franco et al [41] established that MDA-MB-231 cell colony formation is reduced more efficiently by 70 nM of doxorubicin compared to 70 nM of paclitaxel. Alkaloid aloperine derived from plants could inhibit MDA-MB-231 cell colony formation number up to ~40% compared to the control; however, at rather high concentration of 400 µM [42].…”
Section: Anticancer Activitymentioning
confidence: 99%